(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2012)
Story construction ona given title ‘Kusangati Ka Phal’ is an item where the students were asked todesign a story corresponding to the nature of the title given. They wereinstructed to write an original story. Five minutes has been provided to make astory on said proverb. Through this itemthe ideational fluency, Originality and elaboration were assessed. Story with bothendings happy as well as tragic. Inthis item, the subjects are asked to write stories on said situation. The ideabehind this item is to test the imagination of students on the theme in bothways and end I in two different manners. Ten minutes has been provided to makea story on said situation. Through this item the ideational fluency,Originality and elaboration were assessed. Story on ‘Iftoy would speak’ students wereasked to imagine and construct a story. This item also measuresideational fluency, originality and elaboration. The time allotted for the itemis 5 minutes.